LET'S SHARE THE GOODNESS: IMPLEMENTING NOBLE IMPORTANCES FROM AN EARLY AGE THROUGH AN INNOVATIVE PROGRAM AT AL IRSYAD KINDERGARTEN BANYUWANGI - Fidya Salim Bakrisuk; Muhammad Turhan Yani; Achmad Sya’dullah (CV. ADIBA AISHA AMIRA, 2024)
Childhood is a crucial period in developing noble morals in children. Kindergarten Al Irsyad Banyuwangi launched an innovative program called Let's Share Kindness to achieve this goal. This program uses interactive and fun learning methods, encourages children to be active in activities, and gets full support from teachers and parents. This research uses a qualitative case study method to evaluate the effectiveness of the program. The research results show that the Let's Share Goodness program is effective in instilling good values and commendable behavior in accordance with religious teachings in early childhood. This is evidenced by an increase in enthusiasm for learning and playing, a sense of caring and empathy, a sense of gratitude and responsibility, respect and affection, and children's understanding of religious and moral values. Suggestions for increasing the effectiveness of the Let's Share Goodness program are to increase the variety of activities, strengthen cooperation between teachers, parents and the community, empower teachers, and conduct regular program evaluations.